1988
DOI: 10.3171/jns.1988.69.6.0839
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of the proliferative potential of low-grade astrocytomas

Abstract: The proliferative potential of low-grade astrocytomas was estimated in 47 patients. Each patient received an intravenous infusion of bromodeoxyuridine (BUdR), 150 to 200 mg/sq m, at the time of craniotomy to label cells in deoxyribonucleic acid (DNA) synthesis; the percentage of S-phase cells, or BUdR labeling index (LI), of each tumor was determined immunohistochemically. In 29 patients (60%), the tumors had BUdR LI's of less than 1%, indicating a slow growth rate; only three (10%) of these patients died of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…4,10,11,12 Several studies have given a cut off value for MIB-labeling index beyond which prognosis was poor. Montine et al 21 reported that a MIB-LI >7.5% was associated with higher histological grade and poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,11,12 Several studies have given a cut off value for MIB-labeling index beyond which prognosis was poor. Montine et al 21 reported that a MIB-LI >7.5% was associated with higher histological grade and poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the trend is not apparent until 3-4 years follow-up could be interpreted as being a consequence of the time needed for the p53-positive subclone to outgrow the rest of the p53-negative neoplastic cell population. The long time needed for the p53-positive subclone to overgrow the other cells could be related to the low proliferative activity of low-grade astrocytomas (Giangaspero et al, 1987;Hoshino et al, 1988;Allegranza et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Among these parameters are the proliferative activity (Burger et al, 1986;Giangaspero et al, 1987;Hoshino et al, 1988;Allegranza et al, 1991;Jaros et al, 1992), DNA content (Nishizaki et al, 1989) and alterations of oncogenes and tumour-suppressor genes (BaugnetMahieu et al, 1990;Venter & Thomas, 1991;Orian et al, 1992;Jaros et al, 1992;Haapasalo et al, 1993).…”
mentioning
confidence: 99%
“…Infiltration, anaplasia, and recurrences of tumors are linked to There is increasing evidence that the LI carries clinical significance, the higher the LI the more ominous the prognosis. 6 -7 ' 39 The course of a brain tumor is influenced by multiple factors such as size, location, age, degree of edema, necrosis, 7 vascularity, 7 and invasiveness. 40 Nevertheless, the cellular proliferative potential, determined by Ki-67 immunohistochemistry, should be added to the armamentarium of the neuropathologist in the routine assessment of surgical material to provide dynamic cytokinetic data that will complement classical histopathologic diagnosis based upon morphology alone.…”
Section: Discussionmentioning
confidence: 99%
“…6 Early studies of brain tumor cytokinetics were performed with a pulse of 3 H-thymidine, a marker of the S-phase, given to the patient before surgical removal of the tumor. 2 -5 Modern immunohistochemical techniques using commercially available monoclonal antibodies to BUdR, a thymidine analogue, provide a rapid, reproducible method to perform cell kinetics in situ in human 7 -910 and experimental 8 brain tumors; the tumor labeling index is similar by either BUdR immunohistochemistry comparable to 3 H-thymidine autoradiography. 8 A recent advance in cytokinetic analysis of tumors is the introduction of a monoclonal antibody, Ki-67, that recognizes a nuclear antigen expressed in all phases of the cell cycle, but is absent in quiescent G 0 cells.…”
mentioning
confidence: 99%